Numerical solution of Kolmogorov equation using compact - Pooyandeh, Sara; Radpoor, Marzieh Karimi (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this study, we solve the Kolmogorov equation by a compact finite difference method. We apply a compact finite difference approximation for discretizing spatial derivatives. Then, using cubic C 1 -spline collocation technique, we solve the time integration of the resulting system of ordinary differential equations. This joined method has fourth-order accuracy in both space and time variables, that is this method is of order O(h 4 , k4 ). The numerical results confirm the validity of this method